Toxicity assessment of industrial chemicals and airborne contaminants - Khalil, C. (2005)
Exposure to occupational and environmental contaminants is a major contributor to human health problems. Inhalation of gases, vapors, aerosols, and mixtures of these can cause a wide range of adverse health effects, ranging from simple irritation to systemic diseases. Despite significant achievements in the risk assessment of chemicals, the toxicological database, particularly for industrial chemicals, remains limited. Considering there are approximately 80,000 chemicals in commerce, and an extremely large number of chemical mixtures, in vivo testing of this large number is unachievable from both economical and practical perspectives. While in vitro methods are capable of rapidly providing toxicity information, regulatory agencies in general are still cautious about the replacement of whole-animal methods with new in vitro techniques. Although studying the toxic effects of inhaled chemicals is a complex subject, recent studies demonstrate that in vitro methods may have significant potential for assessing the toxicity of airborne contaminants. In this review, current toxicity test methods for risk evaluation of industrial chemicals and airborne contaminants are presented. To evaluate the potential applications of in vitro methods for studying respiratory toxicity, more recent models developed for toxicity testing of airborne contaminants are discussed.